The Role of Islamic Principles in Promoting Sustainable Operations in The Business Sector Among Muslim Millennials - Herianti, Herianti; Awaluddin, Murtiadi; Sumarlin, Sumarlin (International Journal of Business Economics (IJBE), 2024)
Purpose – This research investigates how integrating Islamic principles—emphasizing ethics, social justice, and environmental care—into business practices can promote sustainability, especially among Muslim millennials. The study aims to develop guidelines for incorporating these values into business operations.Methodology – Data were collected over two months (July-August 2023) via online questionnaires distributed to Indonesian Muslim millennials through social media and WhatsApp. The sample size was sufficient for multivariate analysis. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The analysis included measurement model evaluation for validity and reliability and structural model analysis for statistical significance and predictive relevance.Findings – The study found that applying Islamic principles significantly enhances sustainability in business practices, particularly for Indonesian Muslim millennials. The analysis confirmed the validity and reliability of the data and demonstrated that the model not only met statistical significance criteria but also had robust predictive relevance, thereby reinforcing the reliability of the study's findings.Originality/Novelty – This research is unique in its focus on applying Islamic principles to modern business practices for sustainability, mainly targeting the Muslim millennial generation. It provides a detailed framework and new insights into integrating these principles, bridging gaps in existing literature and sparking new interest in the field.Implications – The study provides a practical framework for businesses to align with ethical and environmental standards while respecting cultural values. It also offers actionable recommendations for enhancing sustainability and social responsibility, thereby demonstrating the practical usefulness of the research.